2005
DOI: 10.1007/s10384-004-0135-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Additive Effect of Bunazosin on Latanoprost in Primary Open-Angle Glaucoma

Abstract: There are reports of an additive effect in the lowering of intraocular pressure (IOP) of bunazosin, a selective alpha-1 adrenergic antagonist, on latanoprost, a derivative of 62 Jpn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…2,18 Although the mechanisms of action on the uveoscleral route are different between latanoprost (by remodeling of matrix metalloproteinase) and nipradilol (by relaxation of ciliary muscles and dilatation of spaces between muscle bundles), both drugs decrease IOP via the uveoscleral route. Maruyama et al 19 reported that bunazosin, an alpha-1 blocking agent, has an additive effect when used in combination with latanoprost, but its additive effect is partial, since the IOP reduction obtained after addition of bunazosin is less than that obtained with bunazosin alone. We found that nipradilol 0.25% was less potent than carteolol 2% when used in combination with latanoprost, which may indicate that the alpha-1 blocking effect of nipradilol is not completely additive to latanoprost, as is seen with bunazosin.…”
Section: Discussionmentioning
confidence: 96%
“…2,18 Although the mechanisms of action on the uveoscleral route are different between latanoprost (by remodeling of matrix metalloproteinase) and nipradilol (by relaxation of ciliary muscles and dilatation of spaces between muscle bundles), both drugs decrease IOP via the uveoscleral route. Maruyama et al 19 reported that bunazosin, an alpha-1 blocking agent, has an additive effect when used in combination with latanoprost, but its additive effect is partial, since the IOP reduction obtained after addition of bunazosin is less than that obtained with bunazosin alone. We found that nipradilol 0.25% was less potent than carteolol 2% when used in combination with latanoprost, which may indicate that the alpha-1 blocking effect of nipradilol is not completely additive to latanoprost, as is seen with bunazosin.…”
Section: Discussionmentioning
confidence: 96%
“…Of these, 65 had to be excluded for reasons summarized in table 2 . After the completed selection process, 9 randomized clinical trials which met our inclusion criteria were included in the systematic review [15][16][17][18][19][20][21][22][23] .…”
Section: Resultsmentioning
confidence: 99%
“…Attempts were made to contact the authors for these 6 studies and for 5 of 6 studies, sponsorship disclosure was obtained and classified as nonindustry. [6][7][8][9][10] The single study without sponsorship disclosure 11 and for which no feedback from the authors was obtained was excluded, thereby leaving 43 articles with 64 IOP data sets for analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the low number of eligible data sets for bimatoprost and travoprost, statistical analysis was performed only for the latanoprost IOP data sets (47 IOP data sets from 38 articles) ( Table 1). The 33 IOP data sets from 29 articles (4 studies were cross-over designs and contributed 2 IOP data sets each) investigating latanoprost provided 1-month data, 4,6,8,9, and 14 data sets from 13 articles (1 study was a cross-over design and contributed 2 data sets) provided 3-month data. [7][8][9][10]15,18,[37][38][39][40][41][42][43] Details of the latanoprost studies are provided in Table 2.…”
Section: Resultsmentioning
confidence: 99%